2003
DOI: 10.1590/s1519-69842003000400018
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of entomogen galls in plants from natural vegetation areas in Delfinópolis, MG, Brazil

Abstract: In the present work we aimed to register the occurrence of galls, inductors, inquilines, and parasitoids in plants of three natural vegetation areas in Delfinópolis, MG, Brazil. Results obtained showed 22 types of galls collected from leaf, vein leaf, petioles, stem, and inflorescence of nineteen species belonging to fifteen distinct families. Concerning gall morphology, the following were collected: globoid, conicle, discoidal, fusiform, shell-shape, indefinite, and one substituition of an ovary by an immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
25
1
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 10 publications
(9 reference statements)
5
25
1
8
Order By: Relevance
“…The fact that 75% of the galls have been found in leaves, corroborate the pattern found in studies in Brazil, that indicates the leaf as organ most commonly attacked by gall makers (Maia et al 2008, Maia 2001, Urso-Guimarães et al 2003, Fernandes & Negreiros 2006 and with the world pattern found by Mani (1964). This pattern of occurrence in the leaves happens because the leaves are abundant resources and constant (Maia 2001), besides having a continuous flow of nutrients needed for the maintenance of photosynthesis (Whitham 1978).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The fact that 75% of the galls have been found in leaves, corroborate the pattern found in studies in Brazil, that indicates the leaf as organ most commonly attacked by gall makers (Maia et al 2008, Maia 2001, Urso-Guimarães et al 2003, Fernandes & Negreiros 2006 and with the world pattern found by Mani (1964). This pattern of occurrence in the leaves happens because the leaves are abundant resources and constant (Maia 2001), besides having a continuous flow of nutrients needed for the maintenance of photosynthesis (Whitham 1978).…”
Section: Discussionsupporting
confidence: 85%
“…These data reinforce Urso-Guimarães et al (2003) whose found parasitic Hymenoptera in all galls with trichomes of their study, not sharing the hypothesis of Fernandes & Price (1988) who attribute the presence of trichomes protection against parasitoids.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations